2019
DOI: 10.1186/s13072-018-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Specific functions of TET1 and TET2 in regulating mesenchymal cell lineage determination

Abstract: BackgroundThe 5 hydroxymethylation (5hmC) mark and TET DNA dioxygenases play a pivotal role in embryonic stem cell differentiation and animal development. However, very little is known about TET enzymes in lineage determination of human bone marrow-derived mesenchymal stem/stromal cells (BMSC). We examined the function of all three TET DNA dioxygenases, responsible for DNA hydroxymethylation, in human BMSC cell osteogenic and adipogenic differentiation.ResultsWe used siRNA knockdown and retroviral mediated enf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 56 publications
5
69
0
Order By: Relevance
“…(71) Future work will be needed to test whether such a rewiring occurs in chondrogenesis, as well upon genetic loss of TET1. TET2 and TET3 have already been shown to be important in adult mesenchymal stem cell (MSC) differentiation (72)(73)(74) ; however, their unique contributions vis-à-vis TET1 remain to be explored. Additionally, in the KD of Tet1, we observed that 72% of differentially expressed genes were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…(71) Future work will be needed to test whether such a rewiring occurs in chondrogenesis, as well upon genetic loss of TET1. TET2 and TET3 have already been shown to be important in adult mesenchymal stem cell (MSC) differentiation (72)(73)(74) ; however, their unique contributions vis-à-vis TET1 remain to be explored. Additionally, in the KD of Tet1, we observed that 72% of differentially expressed genes were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there is a lack of information about DNA methylation-based mechanisms that may contribute to MM progression and subsequent bone defects. DNA methylation is an essential epigenetic modification involving the addition of a methyl group to the 5-carbon of the cytosine ring by a family of DNA methyltransferase (DNMT) enzymes 21 , which has been described to play a critical role in MSC lineage determination 22 , as well as in tumor progression and immunosuppression in other cancer types 23 ..…”
Section: Introductionmentioning
confidence: 99%
“…The exact reasons for the SETD4 KO-attenuated differentiation potentials were not clear. Change in genomic methylation status may alter the activity of differentiation linage-determined transcription factors [25][26][27], which may help in elucidating this phenotype. We take cardiomyocyte differentiation factors Nkx2.5 and Gata4 as a sample for discussion below.…”
Section: Discussionmentioning
confidence: 99%